A Delphi Consensus on Clinical Features, Diagnosis, and Treatment of Chronic Rhinosinusitis With Nasal Polyps in the ASEAN Region - Baharudin, Abdullah; Revadi, Govindaraju; Salina, Hussain; Jin Keat, Seow; Pongsakorn, Tantilipikorn; Neville Wei, Yang Teo; De Yun, Wang; Deasi, Anggraini; Tze Choong, Charn; David Chin, Chao‐Wu; Dichapong, Kanjanawasee; Maung Maung, Khaing; et al. (John Wiley & Sons Ltd., 2025)
Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) impacts patients' concentration, ability to work, and overall quality of life. Current treatment options include topical and oral medications, and surgery. Recent evidence supports the efficacy of biologics in improving symptoms and quality of life. This study addresses the lack of consensus in the ASEAN region, providing guidance for otolaryngologists on appropriate CRSwNP management. Methods: A modified Delphi panel was conducted to gather expert opinion and establish consensus on the use of biologics and management of CRSwNP among otolaryngologists in the ASEAN region. Statements were developed based on a literature review and inputs from a Steering Committee of eight experts from Malaysia, Singapore, and Thailand. A three‐stage process was utilized for consensus generation: two online surveys for voting by at least 12 panelists from seven ASEAN countries, followed by moderated online Consensus Meetings with the Steering Committee. Results: Consensus was achieved on 61/69 statements (88%). In Rounds 1 and 2, 37/67 statements (55%) and 13/28 statements (46%) achieved consensus, respectively. During the moderated Consensus Meetings, consensus was achieved on 12/16 statements (75%). Key aspects addressed include symptoms, comorbidities, diagnosis, and treatment pathways, with a focus on biologics. Eligibility criteria and considerations for biologic use were also defined. Conclusions: Insights from this Delphi consensus provide guidance on biologic use for managing CRSwNP in the ASEAN region. Future efforts, such as developing a regional guideline, continued medical education, and further research are essential for appropriate biologic use.